Comparison of C-reactive protein among controlled, moderately controlled and uncontrolled diabetic subjects in a Bangladeshi population (Bangladesh Journal of Medical Biochemistry, 2013)
Poor glycemic control is significantly associated with the development of macrovascular complications of diabetes. C-reactive protein (CRP) is considered as a sensitive and independent risk factor for cardiovascular events. The aim of this study was to compare elevated CRP among controlled, moderately controlled and uncontrolled diabetic subjects in a Bangladeshi population. CRP and glycosylated hemoglobin A1c (HbA1c) were measured in 226 confirmed diabetic subjects purposively and randomly. Elevation of CRP in the moderately controlled (relative risk 1.64, P